KEEFEKTIFAN MEDIA FILM PENDEK VERSI EAGLE AWARDS DALAM PEMBELAJARAN MENULIS PARAGRAF ARGUMENTATIF: Penelitian Eksperimen Semu terhadap Siswa Kelas X SMA PGRI 1 Bandung Tahun Ajaran 2012/2013 - Talitha, Stella (2013)
This research begins with problems: 1) how students ' ability in writing argumentative paragraph in class experiments using media short film version of the Eagle Awards?; 2) how students ' ability in writing argumentative paragraph in the control class use media image?; and 3) how the effectiveness of the use of the short film medium version of the Eagle Awards in learning argumentative paragraph writing? As for the hypothesis that is used in this research is the use of the learning media short film version of the Eagle Awards are effective in learning to write argumentative paragraph in class experiments. The chosen research methods is artificial experiments. This study used two groups of the subject, namely the class of experiments and classroom control. The population in this research is a class X 1 PGRI Bandung HIGH SCHOOL with the class X 4 samples as experiment class and class X 3 as the class of the control. Samples from each class as many as 30 people. Stages of research, among others, to identify issues, conduct prates, giving the treatment three times, and do pascates with the results of paragraph argumentative. As for the measuring instrument used to measure the success of the media made a short film version of the Eagle Awards, namely paragraph argumentative student results. Based on research results, obtained the result that students ' ability in writing argumentative paragraph before getting treatment is the use of the short film medium version of the Eagle Awards in the experimental classes have an average score of 41,83 and after treatment average score be for 58,9. The control class to obtain an average value of 37,69 and pascates 33,46 prates. Hypothesis test results show that the use of the learning media short film version of the Eagle Awards are effective in learning to write argumentative paragraph in class experiments. Penelitian ini diawali dengan permasalahan: 1) bagaimana kemampuan siswa dalam menulis paragraf argumentatif di kelas eksperimen yang menggunakan media film pendek versi Eagle Awards?; 2) bagaimana kemampuan siswa dalam menulis paragraf argumentatif di kelas kontrol yang menggunakan media gambar?; dan 3) bagaimana efektivitas penggunaan media film pendek versi Eagle Awards dalam pembelajaran menulis paragraf argumentatif? Adapun hipotesis yang digunakan dalam penelitian ini adalah penggunaan media pembelajaran film pendek versi Eagle Awards efektif dalam pembelajaran menulis paragraf argumentatif di kelas eksperimen. Metode penelitian yang dipilih adalah eksperimen semu. Penelitian ini menggunakan dua kelompok subjek penelitian, yaitu kelas eksperimen dan kelas kontrol. Populasi dalam penelitian ini adalah kelas X SMA PGRI 1 Bandung dengan sampel kelas X4 sebagai kelas eksperimen dan kelas X3 sebagai kelas kontrol. Sampel dari masing-masing kelas sebanyak 30 orang. Tahapan penelitian antara lain mengidentifikasi masalah, melakukan prates, memberikan perlakuan sebanyak tiga kali, dan melakukan pascates dengan hasil paragraf argumentatif. Adapun alat ukur yang digunakan untuk dijadikan ukuran keberhasilan media film pendek versi Eagle Awards yaitu hasil paragraf argumentatif siswa. BerdasarKan hasil penelitian, diperoleh hasil bahwa kemampuan siswa dalam menulis paragraf argumentatif sebelum mendapatkan perlakuan penggunaan media film pendek versi Eagle Awards di kelas eksperimen memiliki rata-rata skor sebesar 41,83 dan sesudah mendapatkan perlakuan skor rata-rata menjadi sebesar 58,9. Untuk kelas kontrol memperoleh nilai rata-rata prates 37,69 dan pascates 33,46. Hasil uji hipotesis menunjukkan bahwa penggunaan media pembelajaran film pendek versi Eagle Awards efektif dalam pembelajaran menulis paragraf argumentatif di kelas eksperimen.